Graphene Oxide Film as Passive Q-switcher in Erbium-doped Fiber Laser Cavity - Che Mat, Fauziah; Yasin, Moh; Abdul Latiff, Anas; Harun, Sulaiman Wadi (Photonics Letters of Poland, 2017)
All-fiber passively Q-switched fiber lasers have been demonstrated by using graphene oxide (GO) Q-switcher for possible applications in telecommunication, laser processing, fiber sensing and medical community. The GO material was obtained through a modified Hummers method from expanded acid washed graphite flakes and it was embedded into a polyvinyl alcohol (PVA) film to form a saturable absorber (SA) device. The Q-switched pulse operates at 1563.3 nm with a repetition rate that can be tuned from 44.33 kHz to 61.77 kHz as the pump power changes from 39 mW to 96 mW. The highest repetition rate of 61.77 kHz is achieved at a pump power of 96 mW and it is observed that the Q-switched pulse produced maximum pulse energy of 0.054 nJ and pulse width of 5.57 ?s at 96 mW pump power. Full Text: PDF References J. Zayhowski and C. Dill, "Coupled-cavity electro-optically Q-switched Nd:YVO4 microchip lasers", Optics letters 20, 716 (1995). CrossRef C.-x. Gao, W. Zhao, Y.-s. Wang, S.-l. Zhu, G.-f. Chen, and Y.-g. Wang, "Passive Q-switched fiber laser with SESAM in ytterbium-doped double-clad fiber", 27th International congress on High-Speed Photography and Photonics, 62794G (2007). CrossRef M. Ahmed, N. Ali, Z. Salleh, A. Rahman, S. Harun, M. Manaf, "Q-switched erbium doped fiber laser based on single and multiple walled carbon nanotubes embedded in polyethylene oxide film as saturable absorber", Optics & Laser Technology 65, 25 (2015). CrossRef S. Harun, M. Ismail, F. Ahmad, M. Ismail, R. Nor, N. Zulkepely, et al., "A Q-switched erbium-doped fiber laser with a carbon nanotube based saturable absorber", Chinese Physics Letters 29, 114202 (2012). CrossRef A. Martinez and Z. Sun, "Nanotube and graphene saturable absorbers for fibre lasers", Nat Photon 7, 842 (2013). CrossRef J. Boguslawski, J. Sotor, G. Sobon, R. Kozinski, K. Librant, M. Aksienionek, et al., "Graphene oxide paper as a saturable absorber for Er- and Tm-doped fiber lasers", Photonics Research 3, 119 (2015). CrossRef H. Ahmad, F. D. Muhammad, M. Z. Zulkifli, and S. W. Harun, "Q-switched pulse generation from an all-f iber distributed Bragg reflector laser using graphene as saturable absorber", Chinese Optics Letters 11, 071401 (2013). CrossRef